20s & 30s : entertainment for all - Parker, Steve (Milwaukee, Wis. : Gareth Stevens, 2002)
Traces the developments in the entertainment field during the 1920s and 1930s, exploring the new publishing methods and the rise of photojournalism.
Includes bibliographical references (p. 31) and index.
7.0
3-6
Keywords: Entertainment industry -- United States -- History -- Juvenile literature; Entertainment industry -- History; Entertainment industry -- History